EFEKTIFITAS POSISI PERSALINAN SETENGAH DUDUK DAN MIRING KIRI TERHADAP LAMA PERSALINAN KALA II DI KLINIK BIDAN HELEN TARIGAN KEC. MEDAN SELAYANG DAN KLINIK PRATAMA NIAR KEC. MEDAN AMPLAS TAHUN 2020 - Kumalasari; Lubis, Rismahara; Rahmah, Maulida (Poltekkes Kemenkes Medan, 2021)
In Indonesia the MMR is still high, namely 305/100,000 lives birth (Ministry of Health, 2018) In 2017 out of 34 provinces in Indonesia, North Sumatra was among the 6 provinces with a high MMR (Ministry of Health, 2017). In 2017, the MMR in North Sumatara amounted to 58.18 / 100,000 lives birth while in 2018 the MMR increased by a total of 62.18 / 100,000 lives birth (North Sumatra Health Office, 2018). This study aims to determine the effectiveness of semi fowler and lying on the left position to the duration of second stage labor in Helen Tarigan midwifery clinic of Medan Selayang sub district and Niar midwifery clinic of Medan Amplas sub district in 2020. This type of research was pre-experimental with one shot case study / post-test only design. and sampling by purposive sampling, the sample is third trimester pregnant women who will give birth amounting to 22 people. Based on the results of the independent t-test, the value of ? (0.01) <? (0.05) means that the position of semi fowler and lying on the left position of labor in maternal is proven to significantly accelerate the length of the second stage of labor. The average length of second stage of labor in the semi fowler position was 33.63 minutes and the average length of second stage of labor in lying on the left position was 26.44 minutes. Thus, the length of the second stage of labor in the lying on the left position was faster than the semi fowler position with a time difference of 7.19 minutes. Therefore, it can be concluded that the position of semi fowler labor and lying on the left position of labor is effective against the duration of the second stage of labor. It is expected that each midwife recommends using lying on the left of delivery position to accelerate the second stage of labor Keywords : Semi Fowler Birth Position, Lying On The Left Delivery Position, Length of Second Stage of Labor